Character Education Management of Elementary School Students - Wa Ode Mulianti; Dwi Sulisworo; Suardin (The Indonesian Institute of Science and Technology Research, 2023)
The implementation of character education in schools is an effort to enhance the positive character of students. The purposeof this research is to find out the management of character education in 5th-grade students. This type of researchis qualitative descriptive research, with fokus research, namely the management of student character education. Data are obtained through wawancara, observasi, and documentation, then analyzed usinginteractive analysis of kulitative, namely reduction data, data collection, drawing conclusions. The results showed that character education in SD. Laompo State Elementary School was implemented in the scope of learning activities and the creationof school culture, which was carried out systematically through three stages. First, formulating plans for learning programs and programs of school discipline withcharacter. Second, implementing the learning program plan by promising the valueof character into the material and creating a character learning climate, as well as enforcing the implementation of school discipline. Third, measuring student learning development on cognitive, affective and psychomotor aspects, as well as assessing the success of character education programs. Dthe nature of its managementis still subjectto a number of challenges, for which it is necessary to make continuous improvements.